2021
DOI: 10.3389/fneur.2021.764063
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Cerebral Aneurysm Wall Tension and Enhancement Using Finite Element Analysis and High-Resolution Vessel Wall Imaging

Abstract: Biomechanical computational simulation of intracranial aneurysms has become a promising method for predicting features of instability leading to aneurysm growth and rupture. Hemodynamic analysis of aneurysm behavior has helped investigate the complex relationship between features of aneurysm shape, morphology, flow patterns, and the proliferation or degradation of the aneurysm wall. Finite element analysis paired with high-resolution vessel wall imaging can provide more insight into how exactly aneurysm morpho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 42 publications
(47 reference statements)
1
0
0
Order By: Relevance
“…For the same material, the deformation of the three-layer membrane and single-layer membrane structure CA models was basically the same, and the displacement deformation of both membrane structures differed by about 1%. For the same structure, the deformation of the linear elastic material model is larger than that of the hyperelastic material, which is consistent with the results of Galloy et al (2021) . In addition, the calculations showed that the maximum displacements occurred in the intima.…”
Section: Discussionsupporting
confidence: 88%
“…For the same material, the deformation of the three-layer membrane and single-layer membrane structure CA models was basically the same, and the displacement deformation of both membrane structures differed by about 1%. For the same structure, the deformation of the linear elastic material model is larger than that of the hyperelastic material, which is consistent with the results of Galloy et al (2021) . In addition, the calculations showed that the maximum displacements occurred in the intima.…”
Section: Discussionsupporting
confidence: 88%